Adolescent overuse of digital technology: Perspectives of parents, adolescents and practitioners in Qatar - Sanaa Al-Harahsheh (16022323) (2023)
The Doha International Family Institute (DIFI), the World Innovation Summit for Health (WISH) and the World Innovation Summit for Education (WISE) in partnership with Hamad Bin Khalifa University (HBKU), are conducting a research study on the excessive use of digital technologies among adolescents and adults in Qatar and its impact on health, education, and family cohesion. Overuse of technology, informally called digital addiction, is a broad term used to describe excessive, obsessive, compulsive technology use. It has been shown that such use negatively impacts health, education and family relationships. However, the majority of research to date examines this issue in adults; the perspective of adolescents has not been a focus. In this study, we examine the impact of excessive use of digital technologies on family cohesion, relationships within families, children’s health and learning, and what parents and policymakers can do to address this issue. We examine factors that influence children and parents’ excessive use of technology, as well as parents’ strategies and coping mechanisms for dealing with adolescents’ excessive technology use. With the scarcity of validated and specialized approaches to combat the issue, whether in prevention, harm minimization or treatment, we also review the services provided to families, their content, challenges they face, public perception of these services and evidence of success. Other Information License: http://creativecommons.org/licenses/by/4.0/ Additional institutions affiliated with: Technology & Behaviour Research Group (i-Solouk) - CSE